ANALISIS DAYA SAING DAN STRATEGI INDUSTRI FURNITUR ROTAN INDONESIA DI PERDAGANGAN INTERNASIONAL - Dewi, Nike Nurfita; Isharina, Ikhtiara Kaideni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study was to determine the position of competitiveness of Indonesian rattan furniture, the position of Indonesian rattan furniture exports, the export performance of Indonesian rattan furniture, the ability of Indonesian rattan furniture commodities to seize the international trade market, and strategies to increase the competitiveness of the Indonesian rattan furniture industry. The analytical methods used are Revealed Comparative Advantage, Trade Specialization Index, Constant Market Share, Acceleration Ratio, and SWOT Analysis. The results of the Revealed Comparative Advantage (RCA) analysis show that Indonesian rattan furniture has a strong comparative advantage in international trade. The results of the Trade Specialization Index (ISP) analysis show that Indonesia tends to be an exporter of rattan furniture. Constant Market Share (CMS) states that the effect of competitiveness has a strong influence on the growth of Indonesian rattan furniture in international trade. The results of the Acceleration Ratio (AR) analysis show that Indonesia can seize the international trade market share. Based on the results of the Cartesian diagram, the SWOT analysis shows that the export of the Indonesian rattan furniture industry is in quadrant I (one), namely the aggressive strategy.